Chemical Composition and GC-MS Analysis of Essential Oil from Cymbopogon martinii var sonfia - Usman , Md. Rageeb Md.; Vadnere, Gautam P.; Jain, Shreya C.; Wahle, Jaydip; Dhondkar, Ganesh; Ingle, Suraj (Journal of Drug Delivery and Therapeutics, 2025)
Cymbopogon martinii, commonly referred to as palmarosa, is a perennial aromatic grass from the Poaceae family, known for its valuable essential oil rich in geraniol. This oil is in high demand due to its fragrance and potential therapeutic applications. Its versatility enables use in perfumery, cosmetics, and natural remedies. The growing interest in natural products has led to a surge in studies aimed at improving extraction methods and understanding the phytochemical makeup of such oils. The present work aims to extract essential oil from C. martinii var. sofia using steam distillation and to evaluate its chemical composition through GC-MS analysis, thereby determining its quality and commercial viability.Keywords: Cymbopogon martinii var. sofia, essential oil, steam distillation, geraniol, GC-MS analysis, phytochemical constituents.